Peningkatan Kapasitas Masyarakat dalam Pencegahan Judi Online di Desa Kalibaru, Kecamatan Cilincing, Jakarta Utara Tahun 2024 - Ririn Nurhidayanti; Fransiska Milenia Cesarianti; Samsuto Samsuto; Timbo Mangaranap Sirait (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This study aims to analyze the effectiveness of online gambling prevention socialization activities and their impact as well as the establishment of a village corner library in Kalibaru Village, Cilincing District, North Jakarta. Through a participatory method, this research involves the public directly in socialization that discusses the dangers and negative impacts of online gambling, including legal, mental health, and social aspects. In addition, the village corner library was established as a learning center that provides access to related literature to increase public awareness. The results of the study show that socialization and the establishment of libraries significantly increase public knowledge and awareness about the risks of online gambling. The active participation of the community in the socialization and utilization of libraries indicates the success of this intervention. The conclusion of this study is that a community-based approach, through education and literacy improvement, is an effective strategy in preventing online gambling and strengthening people's capacity to face social challenges.